High risk of relapse with intermediate dose cytarabine for consolidation in young favourable‐risk acute myeloid leukaemia patients following induction with 7+3: a retrospective multicentre analysis and critical review of the literature. (11th April 2021) - Kolla, Bhaskar C.; Halim, Nurul A. A.; Cao, Qing; Sachs, Zohar; Warlick, Erica; Weisdorf, Daniel; Ho, Aloysius Y. L.; Chuan, Wong G.; Lao, Zhentang; He, Fiona
Summary: Following the 2017 European LeukemiaNet (ELN) guidelines, we changed our practice from using high‐dose cytarabine (HIDAC‐3 g/m 2 q12h‐D1, 3, 5) to intermediate‐dose cytarabine (IDAC‐1·5 g/m 2 q12h‐D1, 3, 5/D1–3) for consolidation in young(<60 years) favourable‐risk acute myeloid leukaemia (AML) patients. We assessed the clinical impact of this practice change. Of 80 patients, 51 received HIDAC prior to the protocol change, and subsequently, 29 received IDAC. The three‐year risk of relapse was significantly higher with IDAC [61%; 95% confidence interval (CI) 40–82] compared with HIDAC (22%; 10–34), P < 0·01. Our findings suggest HIDAC, rather than IDAC, is the preferred dose for single‐agent cytarabine consolidation in young, favourable‐risk AML following 7+3 induction.